RELATIONSHIP BETWEEN WORK SATISFACTION AND WORK ENGAGEMENT: A STUDY OF MARKETING DEPARTMENT IN PT BANK SWASTA C (JAKARTA) - M, Safitri; Ismiyah; Mariyanti, Sulis; Budiawan, Andi (International Journal of Psychosocial Rehabilitation, 2020)
Marketing employees are the key or top priority for the success of a company. The work of marketing employees in the banking business are inseparable from the targets set by the company. The inability to reach the target makes the employees of marketing not engaged in their work. One factor that influences work engagement is job satisfaction. The purpose of this study was to determine the relationship between job satisfaction with work engagement among marketing employees at PT Bank Swasta C in Jakarta. The design of this study was a correlation study with a purposive sampling technique with a sample size of 115. Job satisfaction was measured using the theory of Luthans (2006) with reliability (α) = 0.936 as many as 31 valid items. Work engagement scale based on the theory of Schaufeli and Bakker (2002) with reliability (α) = 0.948 as many as 21 valid items. The results showed there was a positive and significant relationship of job satisfaction with work engagement (sig 0,000 and r = 0.524). The contribution of job satisfaction in influencing work engagement by 27.5%. The job satisfaction of PT Bank Swasta C marketing employees in Jakarta was higher (54.8%) while work engagement was lower at 51.3%. From the results of the study that there is no relationship between work engagement with gender, age, work period and marital status.